Case Report on Pulmonary Involvement in a Patient with Adult Still’s Disease - Dvoretsky, Leonid; Torgashina, Anna; Rachina, Svetlana; Dubrovskaya, Nelli; Hewathanthirige, Girindu (Current Rheumatology Reviews, 2023)
Background: Pulmonary manifestations and lung impairment are rarely associated with the Adult Still's Disease and are reported in less than 5%. Case Presentation: The present clinical case describes the Adult Still's Disease with pulmonary involvement in a 45- year-old male. The main clinical manifestations included continuous fever, failure to respond to antibiotic therapy, skin rashes, musculoskeletal syndrome and pharyngitis. Additionally, bronchopulmonary lymphadenopathy, interstitial changes and dense foci with clear contours were detected in the lungs. Laboratory abnormalities included neutrophilic leukocytosis, increased ALT, AST, and elevated serum inflammatory marker levels. A cyclical course characterised the disease with strictly defined time intervals between flare-ups and remissions. After the prescription of methylprednisolone with the subsequent addition of methotrexate, complete regression of clinical symptoms, normalization of laboratory tests, and partial regression of computed tomography findings in the lungs were observed. Conclusion: Despite the low incidence, pulmonary involvement is an unfavorable manifestation of Adult Still's Disease. An individual feature of this case report was the asymptomatic lung involvement manifested only by changes revealed through computed tomography. For a long time, flareups of the disease were considered bacterial infections of unclear nature requiring systemic antibiotics.
Keywords: lymphadenopathy